Clustering of death receptors in lipid rafts initiates neutrophil spontaneous apoptosis. (26th October 2004) - Scheel-Toellner, D.; Wang, K.; Assi, L.K.; Webb, P.R.; Craddock, R.M.; Salmon, M.; Lord, J.M.
Abstract : Neutrophils die by apoptosis spontaneously within 12–24 h of their release from the bone marrow. The mechanism regulating entry of neutrophils into apoptosis at the end of their life-span is currently under debate. Our data suggest that neutrophil apoptosis involves a novel mechanism of caspase 8 activation that is indirectly regulated by accumulation of reactive oxygen species. We detected early activation of caspase 8 upstream of caspase 3 activation, suggesting death receptor signalling. The CD95 DISC (death-inducing signalling complex) was detected in neutrophils, but blocking antibodies to death receptors did not inhibit apoptosis, suggesting a novel mechanism for caspase 8 activation. Death receptor clustering in ceramide-rich lipid rafts is thought to be an early event in their signalling, so we investigated the role of ceramide generated by ASM (acid sphingomyelinase) in neutrophil apoptosis. Ceramide was generated early in neutrophil apoptosis, and ASM activity was required for neutrophil apoptosis. Moreover, neutrophil apoptosis was significantly delayed in ASM −/− mice compared with their wild-type littermates. CD95 DISC components were present in lipid rafts in neutrophils, and were progressively clustered in cultured neutrophils. Generation of ceramide was blocked by desferrioxamine, suggesting that hydroxyl radicals are important for the activation of ASM. This observation was in line with our earlier observation of a precipitous drop in reduced glutathione in the aging neutrophil.